2016
DOI: 10.33393/dti.2016.1420
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Organizing Pneumonia (OP) Associated with Pembrolizumab

Abstract: Until recently, chemotherapy for metastatic melanoma had disappointing results. The identification of immune checkpoints such as CTLA-4 and PD-1/PD-L1 has led to the development of an array of monoclonal antibodies (Mabs). These immunologic approaches against tumoral cells come with a novel kind of side effects that the clinician needs to be familiarized with. Herein, we report for the first time a case of organizing pneumonia, based on imaging and cytological analyses of bronchoalveolar lavage, possibly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Airspace disease may manifest as either consolidative or ground-glass opacities or a combination of both, frequently depicted on air bronchograms with or without a component of bronchial dilatation. A circumferential consolidative opacity surrounding an interior area of ground-glass attenuation (ie, reversed halo or atoll sign), a relatively specific marker for OP in the nontreatment setting, has also been reported in ICI therapy-related pneumonitis (32). Airspace disease can also be migratory, changing location or configuration over time (33).…”
Section: Op Patternmentioning
confidence: 99%
“…Airspace disease may manifest as either consolidative or ground-glass opacities or a combination of both, frequently depicted on air bronchograms with or without a component of bronchial dilatation. A circumferential consolidative opacity surrounding an interior area of ground-glass attenuation (ie, reversed halo or atoll sign), a relatively specific marker for OP in the nontreatment setting, has also been reported in ICI therapy-related pneumonitis (32). Airspace disease can also be migratory, changing location or configuration over time (33).…”
Section: Op Patternmentioning
confidence: 99%
“…The COP pattern typically manifests with multifocal consolidation and GGOs in a predominantly peripheral distribution ( Fig 5). The hypersensitivity pneumonitis pattern manifests with diffuse GGOs and centrilobular nodularities and may also include air trapping ( Fig 6) (7,21,(23)(24)(25)(26)(27)(28).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…More recently, a case of OP was described in a melanoma patient treated with nivolumab [ 11 ]. Only two cases of pulmonary side effects with pembrolizumab have thus far been described: one case of OP occurring after four infusions and one case of mediastinal granulomatosis [ 13 15 ]. In clinical trials of pembrolizumab and nivolumab, the majority of pneumonitis cases have been reported as mild to moderate in severity, but one death has occurred [ 2 4 , 10 ].…”
mentioning
confidence: 99%